Legal framework as a conditioning factor underlying the exploitation of agrotourism and ecotourism: an analysis of current conditions in Russia and Belarus - Vetrova, Ekaterina; Vasyukov, Vitalii; Otcheskiy, Ivan; Deyev, Alexey; Sakhno, Aleksandr; Panova , Aleksandra (Anais Brasileiros de Estudos Turísticos, 2022)
This paper considers various possibilities and prospects for the development of agricultural and ecotourism in Russia. In the context of financial and logistical constraints on the Russian business, the closure of many traditional tourist destinations necessitates a reorientation of tourist flows both in terms of location and in terms of tourist interest. Currently, travelers are inclined to choose new types of tourism, including agrotourism and ecotourism. Agrotourism and ecotourism can become a significant economic component for several agricultural and natural areas. The study demonstrates that the closure of traditional tourist destinations for Russian tourists creates unique conditions for the redirection of tourist flows and the qualitative reorientation of tourism. The main tasks of regulation in this area are streamlining relations in the following combination "agricultural and natural territories – tourism business – a consumer of a tourism product (tourist)", as well as observing the legitimate interests of all participants in such relations. The authors of the article study positive global experience in the organization and regulation of agrotourism and ecotourism. They also propose some legal formulations for the formation of legal concepts aimed at supporting the development of the tourism business in both agricultural and environmental areas.